Victimization, Abuse, and Socioeconomic Factors in Women’s Incarceration: Insights from A World Apart: Women, Prison, and Life Behind Bars - Ewalefoh, Ernest Osemobho (dialektika kontemporer, 2025)
This research delves into the complex interplay of victimization, abuse, and socioeconomic factors in women’s incarceration, using Cristina Rathbone’s A World Apart: Women, Prison, and Life Behind Bars as a foundational case study. The study highlights how past traumas, systemic poverty, and limited access to education and employment opportunities converge to funnel women into the criminal justice system. By examining the lived experiences of women incarcerated at the Massachusetts Correctional Institution-Framingham (MCI-Framingham), this research underscores the cyclical nature of victimization, abuse, and socioeconomic deprivation that often predetermines their incarceration. The study advocates for a transformative approach to criminal justice, emphasizing the need for rehabilitative strategies that address the root causes of criminal behavior among women. By integrating socioeconomic support, mental health services, and educational opportunities, the criminal justice system can foster equitable treatment and disrupt the persistent cycle of crime and punishment. This paper calls for policy reforms that prioritize education, vocational training, and trauma-informed care, aiming to transform not only the lives of incarcerated women but also the broader structures of the criminal justice system. Through this exploration, the study advocates for a more compassionate and comprehensive approach to addressing the unique challenges faced by women in the criminal justice system.